STRATEGI PEMASARAN DAN PELATIHAN KEWIRAUSAHAAN HASIL PERTANIAN SINGKONG DI DESA SUMBERPINANG KECAMATAN PAKUSARI KABUPATEN JEMBER 2024 - Sudarsih, Sudarsih; Aulia N., Ponti Primastuti (Fakultas Ekonomi dan Bisnis, 2024)
Abstract The demand for food in Indonesia is increasing in line with population growth. Indonesia’s abundant natural resources support the development of the food industry. In the Jember region and its surroundings, the potential demand for cassava needs attention. Entrepreneurship in the cassava business involves production factors such as land, labor, capital, and skills. Successful entrepreneurs exhibit creativity, innovation, risk-taking, and a focus on achievement. Entrepreneurship training is essential to nurture independence and guide the younger generation toward creating self-employment opportunities. In the era of globalization, partnership strategies are also relevant for optimizing cassava-based business opportunities through comparative advantages.